PENGARUH DISIPLIN KERJA DAN PENGUASAAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI DI UNIVERSITAS DARMA AGUNG - Pandapotan Na Uli Sun Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This study aims to (1) find out how much influence the work discipline and mastery of information and technology on employee’s performance at Darma Agung University and (2) find out which factors are the most dominant on employee’s performance at Darma Agung University. The theory used is the theory of Human Resource Management related to the behavior of the respondent. The technique of collecting the Primary data is conducted with questionnaires, supported by interviews. The samples in the study are 61 respondents. The research method used is quantitative descriptive. Data processing uses SPSS Version 2.0 software with descriptive analysis and hypothesis testing using multiple linear regression analysis. The coefficient of determination (R²) is 0.21. This shows that the independent variables studied were able to explain 21% of employee performance at Darma Agung University, and the remaining 79% was explained by other variables that were not examined. The results shows that work discipline and mastery of information and technology have a significant effect on performance of the employees at Darma Agung University, and work discipline factors have the most dominant influence on employee’s performance at Darma Agung University